Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories: Summary of a Workshop - National Academy of Sciences; National Research Council (The National Academies Press, 2012)
During July 10-13, 2011, 68 participants from 32 countries gathered in Istanbul, Turkey for a workshop organized by the United States National Research Council on Anticipating Biosecurity Challenges of the Global Expansion of High-containment Biological Laboratories. The United States Department of State's Biosecurity Engagement Program sponsored the workshop, which was held in partnership with the Turkish Academy of Sciences. The international workshop examined biosafety and biosecurity issues related to the design, construction, maintenance, and operation of high-containment biological laboratories- equivalent to United States Centers for Disease Control and Prevention biological safety level 3 or 4 labs. Although these laboratories are needed to characterize highly dangerous human and animal pathogens, assist in disease surveillance, and produce vaccines, they are complex systems with inherent risks. Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories summarizes the workshop discussion, which included the following topics: Technological options to meet diagnostic, research, and other goals; Laboratory construction and commissioning; Operational maintenance to provide sustainable capabilities, safety, and security; and Measures for encouraging a culture of responsible conduct. Workshop attendees described the history and current challenges they face in their individual laboratories. Speakers recounted steps they were taking to improve safety and security, from running training programs to implementing a variety of personnel reliability measures. Many also spoke about physical security, access controls, and monitoring pathogen inventories. Workshop participants also identified tensions in the field and suggested possible areas for action.
Keywords: Conflict and Security Issues; Biology and Life Sciences

Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety: Summary of a Workshop - National Academy of Sciences (The National Academies Press, 2016)
The United States and India have pledged to deepen the linkages between their people, their businesses, and their governments for the mutual benefit of both countries and for the promotion of global peace, stability, economic growth and prosperity. Both nations are now inclined to improve relations and cooperation, but the nations need specific actions that will yield progress and build confidence and momentum for further cooperation. The Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety, held in November 2014, encouraged scientists from both countries to examine global issues related to emerging and existing infections and global health safety, to share experience and approaches, and to identify opportunities for cooperation to improve practice and research in these areas. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Safe Science: Promoting a Culture of Safety in Academic Chemical Research - National Research Council (The National Academies Press, 2014)
Recent serious and sometimes fatal accidents in chemical research laboratories at United States universities have driven government agencies, professional societies, industries, and universities themselves to examine the culture of safety in research laboratories. These incidents have triggered a broader discussion of how serious incidents can be prevented in the future and how best to train researchers and emergency personnel to respond appropriately when incidents do occur. As the priority placed on safety increases, many institutions have expressed a desire to go beyond simple compliance with regulations to work toward fostering a strong, positive safety culture: affirming a constant commitment to safety throughout their institutions, while integrating safety as an essential element in the daily work of laboratory researchers. Safe Science takes on this challenge. This report examines the culture of safety in research institutions and makes recommendations for university leadership, laboratory researchers, and environmental health and safety professionals to support safety as a core value of their institutions. The report discusses ways to fulfill that commitment through prioritizing funding for safety equipment and training, as well as making safety an ongoing operational priority. A strong, positive safety culture arises not because of a set of rules but because of a constant commitment to safety throughout an organization. Such a culture supports the free exchange of safety information, emphasizes learning and improvement, and assigns greater importance to solving problems than to placing blame. High importance is assigned to safety at all times, not just when it is convenient or does not threaten personal or institutional productivity goals. Safe Science will be a guide to make the changes needed at all levels to protect students, researchers, and staff.
Keywords: Math, Chemistry, and Physics; Policy for Science and Technology; Conflict and Security Issues

Prudent Practices in the Laboratory: Handling and Management of Chemical Hazards, Updated Version - National Research Council (The National Academies Press, 2011)
Prudent Practices in the Laboratory—the book that has served for decades as the standard for chemical laboratory safety practice—now features updates and new topics. This revised edition has an expanded chapter on chemical management and delves into new areas, such as nanotechnology, laboratory security, and emergency planning. Developed by experts from academia and industry, with specialties in such areas as chemical sciences, pollution prevention, and laboratory safety, Prudent Practices in the Laboratory provides guidance on planning procedures for the handling, storage, and disposal of chemicals. The book offers prudent practices designed to promote safety and includes practical information on assessing hazards, managing chemicals, disposing of wastes, and more. Prudent Practices in the Laboratory will continue to serve as the leading source of chemical safety guidelines for people working with laboratory chemicals: research chemists, technicians, safety officers, educators, and students.
Keywords: Math, Chemistry, and Physics; Environment and Environmental Studies; Conflict and Security Issues

Strengthening the Disaster Resilience of the Academic Biomedical Research Community: Protecting the Nation's Investment - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The academic biomedical research community is a hub of employment, economic productivity, and scientific progress. Academic research institutions are drivers of economic development in their local and state economies and, by extension, the national economy. Beyond the economic input that the academic biomedical research community both receives and provides, it generates knowledge that in turn affects society in myriad ways. The United States has experienced and continues to face the threat of disasters, and, like all entities, the academic biomedical research community can be affected. Recent disasters, from hurricanes to cyber-attacks, and their consequences have shown that the investments of the federal government and of the many other entities that sponsor academic research are not uniformly secure. First and foremost, events that damage biomedical laboratories and the institutions that house them can have impacts on the safety and well-being of humans and research animals. Furthermore, disasters can affect career trajectories, scientific progress, and financial stability at the individual and institutional levels. Strengthening the Disaster Resilience of the Academic Biomedical Research Community offers recommendations and guidance to enhance the disaster resilience of the academic biomedical research community, with a special focus on the potential actions researchers, academic research institutions, and research sponsors can take to mitigate the impact of future disasters.
Keywords: Conflict and Security Issues

Occupational Health and Safety in the Care and Use of Research Animals - National Research Council (The National Academies Press, 1997)
Much has been written about the care of research animals. Yet little guidance has appeared on protecting the health and safety of the people who care for or use these animals. This book, an implementation handbook and companion to Guide For the Care and Use of Laboratory Animals, identifies principles for building a program and discusses the accountability of institutional leaders, managers, and employees for a program's success. It provides a detailed description of risks—physical and chemical hazards, allergens and zoonoses, and hazards from experiments—which will serve as a continuing reference for the laboratory. The book offers specific recommendations for controlling risk through administrative procedures, facility design, engineering controls, and periodic evaluations. The volume focuses on the worker, with detailed discussions of work practices, the use of personal protective gear, and the development of an emergency response plan. This handbook will be invaluable to administrators, researchers, and employees in any animal research facility. It will also be of interest to personnel in zoos, animal shelters, and veterinary facilities.
Keywords: Biology and Life Sciences

Managing for High-Quality Science and Engineering at the NNSA National Security Laboratories - National Research Council (The National Academies Press, 2013)
The three National Security Laboratories—Los Alamos National Laboratory (LANL), Sandia National Laboratories (SNL), and Lawrence Livermore National Laboratory (LLNL)—are managed by private-sector entities under contract to the National Nuclear Security Administration (NNSA). The FY2010 Defense Authorization Act mandated that NNSA task the National Research Council (NRC) to study the quality and management of Science and Engineering (S&E) at these Laboratories. This study (addressing a total of 5 tasks) is being conducted in two phases. This report covers the first phase, which addresses the relationship between the quality of the science and engineering at the Laboratory and the contract for managing and operating the Laboratory (task 4), and also addresses the management of work conducted by the Laboratory for entities other than the Department of Energy (task 5). The study's second phase will evaluate the actual quality of S&E in key subject areas. Managing for High-Quality Science and Engineering at the NNSA National Security Laboratories presents assessments of the evolution of the mission of the NNSA Labs and the management and performance of research in support of the missions, and the relationship between the Laboratory Directed Research and Development (LDRD) program and the ability of the Labs to fulfill their mission. The report examines the framework for managing science and engineering research at the Labs and provides an analysis of the relationships among the several players in the management of the Labs—the NNSA, the site offices, the contractors, and the Lab managers—and the effect of that relationship on the Laboratories' ability to carry out science and engineering research.
Keywords: Conflict and Security Issues

Design, Implementation, Monitoring, and Sharing of Performance Standards for Laboratory Animal Use: Summary of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
In order to better understand the critical issues pertaining to the concept of performance standards for laboratory animal use, the Institute for Laboratory Animal Research Roundtable on Science and Welfare in Laboratory Animal Use held a public workshop on April 20-21, 2015. The purpose of the workshop was to promote the appropriate and responsible care of animals in research, to provide a balanced and civil forum for discussion and collaboration, and to help build transparency and trust among stakeholders. Participants addressed the challenges of defining, developing, implementing, assessing, and validating performance standards to ensure "optimal practices, management, and operations." This report summarizes the presentations and discussions from the workshop.
Keywords: Biology and Life Sciences

Evaluation of the Health and Safety Risks of the New USAMRIID High-Containment Facilities at Fort Detrick, Maryland - National Research Council (The National Academies Press, 2010)
The U.S. Army Medical Research Institute of Infectious Diseases in Frederick, Maryland, is designed to handle pathogens that cause serious or potentially lethal diseases, which require the research performed on them be contained to specialized laboratories. In 2007 a decision was made to expand those facilities causing concern among area residents that public health and safety risks, and strategies to mitigate those concerns were not adequately considered in the decision to go forward with the expansion. In Evaluation of the Health and Safety Risks of the New USAMRIID High Containment Facilities at Fort Detrick, Maryland a group of experts in areas including biosafety, infectious diseases, industrial hygiene, environmental engineering, risk assessment and epidemiology, explored whether measures were being taken to ensure prevention and mitigation of risk to the health and safety of workers and the public. They also assessed whether the procedures and regulations employed meet accepted standards of the Centers for Disease Control and Prevention and the National Institutes of Health. Evaluation of the Health and Safety Risks of the New USAMRIID High Containment Facilities at Fort Detrick, Maryland evaluates the health and safety aspects of the environmental impact statement developed to support the construction of the new laboratories and explores the institute's operating requirements, medical and emergency management response plans and communication and cooperation with the public. The book recommends that USAMRIID continue to set high standards for advancing security, operational, and biosurety measures, and that additional measures be taken to provide assurance that experienced medical professionals are readily available to consult on unusual infectious diseases. It also suggests that USAMRIID expand its two-way communications with the public.
Keywords: Conflict and Security Issues

Guide for the Care and Use of Laboratory Animals: Eighth Edition - National Research Council (The National Academies Press, 2011)
A respected resource for decades, the Guide for the Care and Use of Laboratory Animals has been updated by a committee of experts, taking into consideration input from the scientific and laboratory animal communities and the public at large. The Guide incorporates new scientific information on common laboratory animals, including aquatic species, and includes extensive references. It is organized around major components of animal use: Key concepts of animal care and use. The Guide sets the framework for the humane care and use of laboratory animals. Animal care and use program. The Guide discusses the concept of a broad Program of Animal Care and Use, including roles and responsibilities of the Institutional Official, Attending Veterinarian and the Institutional Animal Care and Use Committee. Animal environment, husbandry, and management. A chapter on this topic is now divided into sections on terrestrial and aquatic animals and provides recommendations for housing and environment, husbandry, behavioral and population management, and more. Veterinary care. The Guide discusses veterinary care and the responsibilities of the Attending Veterinarian. It includes recommendations on animal procurement and transportation, preventive medicine (including animal biosecurity), and clinical care and management. The Guide addresses distress and pain recognition and relief, and issues surrounding euthanasia. Physical plant. The Guide identifies design issues, providing construction guidelines for functional areas; considerations such as drainage, vibration and noise control, and environmental monitoring; and specialized facilities for animal housing and research needs. The Guide for the Care and Use of Laboratory Animals provides a framework for the judgments required in the management of animal facilities. This updated and expanded resource of proven value will be important to scientists and researchers, veterinarians, animal care personnel, facilities managers, institutional administrators, policy makers involved in research issues, and animal welfare advocates.
Keywords: Biology and Life Sciences; Agriculture